2022
DOI: 10.1186/s12888-022-04120-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to improve medication adherence in adults with depressive disorders: a meta-analysis

Abstract: Background Non-adherence to medication is a major obstacle in the treatment of depressive disorders. We systematically reviewed the literature to evaluate the effectiveness of interventions aimed at improving adherence to medication among adults with depressive disorders with emphasis on initiation and implementation phase. Methods We searched Medline, EMBASE, The Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO, Social Science Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…A series of 4-h group sessions consisting of two interactive online sessions, one month apart, led by a clinical leader along with the principal investigator were set up. The contents and procedures of the sessions were designed based on the results of the literature review carried out in a previous study ( 24 ), selecting the best documented and evaluated interventions providing valid data on the results of adherence to pharmacological treatment and over the long term.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of 4-h group sessions consisting of two interactive online sessions, one month apart, led by a clinical leader along with the principal investigator were set up. The contents and procedures of the sessions were designed based on the results of the literature review carried out in a previous study ( 24 ), selecting the best documented and evaluated interventions providing valid data on the results of adherence to pharmacological treatment and over the long term.…”
Section: Methodsmentioning
confidence: 99%
“…To address adherence issues effectively, multiple approaches consider these factors with the aim of improving medication adherence and treatment outcomes. A recently published systematic review has shown that multicomponent interventions improve short and medium-term adherence to medication among adults with depressive disorders, but there is insufficient evidence in the literature to draw longer-term conclusions ( 24 ). However, the evidence strongly supports the effectiveness of collaborative care in improving adherence among adults with depressive disorders ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the World Health Organization has recognized it to be the leading cause of disability worldwide ( 1 ). Major depressive disorder (MDD) is a form of severe mental dysfunction that affects approximately 6% of adults worldwide and is associated with significant mortality, morbidity, and social costs ( 2 ). Several measures, including psychotherapy, physical therapy, and pharmacotherapy, have been adopted for treating MDD.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Chong and colleagues on interventions aimed at improving adherence to antidepressants reported that multifaceted interventions involving both service user and provider with behavioral component were effective [ 1 ], which was supported by another targeted review [ 13 ]. However, a meta-analysis published recently concluded that the interventions are effective only in the first six months [ 14 ].…”
Section: Introductionmentioning
confidence: 99%